Absolute beginner's guide to project management - Horine, Greg (Absolute beginners guide., 2005)
"Absolute Beginner's Guide to Project Management shares the insights, fundamentals, and techniques that will enable you to manage projects of all types more successfully. Whether you are new to project management, taking on your first project management assignment, an experienced project manager needing a refresher course, or you have limited formal project management education, you'll find this book a great resource."--Jacket.